Insidensi Nematoda Gastrointestinal dan Protozoa pada Monyet Ekor Panjang (Macaca fascicularis) Liar di Taman Wisata Alam (TWA) Pulau Weh Sabang - Rahmi, Erdiansyah; Hanafiah, Muhammad; Sutriana, Amalia; Hambal, Muhammad; Wajidi, Farid (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2010)
The research aims to find out theÂ incidence of gastrointestinal parasite in wild long tail macaque in wildlifeÂ reserveÂ park, WehÂ Island, Sabang. ForÂ that purpose,Â fecalÂ specimensÂ from 25 wildÂ longÂ tail macaquesÂ in WehÂ Island-Â Sabang wereÂ collected.Â TheÂ freshÂ faecesÂ samples wereÂ thenÂ preservedÂ using AFAÂ (alcohol-formal-acetic)Â liquidÂ priorÂ toÂ beÂ examinedÂ inÂ ParasitologyÂ Laboratorium,Â FacultyÂ of Veterinary Medicine, Syiah Kuala University.Â Â TheÂ presence of gastrointestinalÂ parasite wasÂ observed using centrifuge method as well as BorayÂ sedimentation method. The obtained data were tabulated and analyzedÂ descriptively.Â TheÂ resultÂ revealedÂ thatÂ twoÂ parasiteÂ speciesÂ wereÂ foundÂ inÂ gastrointestine; EimeriaÂ spp.Â Â Â (12%)Â andÂ StrongloidesÂ spp.Â (8%).Â ItÂ couldÂ beÂ concludedÂ thatÂ theÂ prevalenceÂ of gastrointestinalÂ parasiteÂ in wildÂ longÂ tail macaqueÂ in wildlifeÂ reserveÂ park, WehÂ Island-Â Sabang was considered mild.